Skor, the winged stallion - Blade, Adam; Tucker, Ezra N. (Scholastic New York, 2010)
"As Tom and Elenna navigate the horrid terrain of Gorgonia, they quickly realize that nothing is what it seems to be. Each step brings them to another dangerous encounter. But Tom won't give up. Not when Epos the Winged Flame is being held captive somewhere in the Dark Realm and Malvel has created a wicket winged Beast of his own. With the help of his friends, Tom is determined to chase down the evil wizard and return all of the good Beasts back to Avantia"--Page 4 of cover